Cross-layer design for video streaming over QoS-enabled WLANs - Guo, Tiantian. (2013)
The high penetration of WLANs has encouraged multimedia applications in the public and the home environment. Among various multimedia applications, video streaming is one of the most popular applications for WLANs. However, the characteristics of wireless communications such as limited bandwidth, time-varying channel conditions, dynamic network users, the contention-based WLAN channel access, and the heterogeneous properties of video traffic make video